Analysis of Seal Face Formation Parameters using Powder Metallurgy Technology with Taguchi Method and Gray Relational Analysis - Kurniawan Kurniawan; Mohammad Nurdin; Otto Purnawarman; Fachrul Rozy (The International Journal of Mechanical Engineering and Sciences, 2022)
The seal face is the main component of a mechanical seal to prevent leakage in a system with fluid flow. Seal face manufacture is generally produced by the material removal process, which causes some raw material waste. Powder metallurgy is the process of manufacturing products from metal powders with raw material efficiency of up to 97%. This study discusses the relationship between the manufacturing process parameters of seal face with SiC material through a powder metallurgy process as a substitute for manufacturing by material removal. The approach used in this research was the design of experiments with the Taguchi method and the technique of Gray Relational Analysis. Process parameters controlled were compaction pressure (CF), compaction time (CH), sintering temperature (ST), and sintering time (SH). Responses were measured in the form of surface hardness (HV) and density. The combination of process parameters that produces the optimum response is CF = 408 N/mm2 (level 3), CH = 2 min (level 1) ST = 1050°C (level 3), SH = 120 min (level 2) with contribution of process parameters CF = 38.06%, CH = 2.53%, ST = 49.50%, and SH = 9.91%. The optimum surface hardness and density values were 513.03 HV and 3.04 gr/mm3.